Depressive Symptoms and Resilience among Pregnant Adolescents: A Case-Control Study - Danny Salazar-Pousada; Dalton Arroyo; Luis Hidalgo; Faustino R. Pérez-López; Peter Chedraui (Hindawi Limited, 2010)
Background. Data regarding depression and resilience among adolescents is still lacking. Objective. To assess depressive symptoms and resilience among pregnant adolescents. Method. Depressive symptoms and resilience were assessed using two validated inventories, the 10-item Center for Epidemiologic Studies Short Depression Scale (CESD-10) and the 14-item Wagnild and Young Resilience Scale (RS), respectively. A case-control approach was used to compare differences between adolescents and adults. Results. A total of 302 pregnant women were enrolled in the study, 151 assigned to each group. Overall, 56.6% of gravids presented total CESD-10 scores 10 or more indicating depressed mood. Despite this, total CESD-10 scores and depressed mood rate did not differ among studied groups. Adolescents did however display lower resilience reflected by lower total RS scores and a higher rate of scores below the calculated median (P<.05). Logistic regression analysis could not establish any risk factor for depressed mood among studied subjects; however, having an adolescent partner (OR, 2.0 CI 95% 1.06-4.0, P=.03) and a preterm delivery (OR, 3.0 CI 95% 1.43-6.55, P=.004) related to a higher risk for lower resilience. Conclusion. In light of the findings of the present study, programs oriented at giving adolescents support before, during, and after pregnancy should be encouraged.